The Impact of Information and Communication Technology Utilisation on Firm Performance: A Case Study of Women Entrepreneurs (Malaysian Management Journal, 2006)
Rapid economic development and globalisation make Information and Communication Technology (ICT) become more important as media of production, marketing, and sourcing information. In this era, the level of computerisation is viewed as crucial for the development of industries. Enterprises that are lagging in the ICT facilities are regarded as out-dated and not progressing. Women entrepreneurs are always seen as lagging behind and there is a wide digital divide among them, hence different levels of performance prevails. This paper attempts to examine this issue through focusing on factors that influence level of ICT utilisation in women owned enterprises and how far this will affect their firm performance. In this paper performance is measured by percentage sales, percentage export, value of sales, and profit earned by the firms. The analysis is based on 200 women entrepreneurs surveyed in 2004 in the Klang Valley. They are involved in various types of manufacturing and services sub-sectors. The study found that the level of ICT utilisation is significantly determined by the entrepreneur’s level of education, period of firm establishment, and firm size. It was also found that capital and labour are the two most important determinants of total sales. Other factors that significantly determine total sales are firm size, ICT workers, Internet usage, and computer usage in the production and accounting management.